Small-scale continuous production of a tropical marine copepod, Nitocra affinis californica Lang and its potential as live food for aquaculture - Matias-Peralta, Hazel Monica; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff; Mohamed, Suhaila (Academic Journals, 2011)
A study to establish a relatively simple and reliable small scale mass production and the nutritional profile of Nitocra affinis was undertaken. The result confirmed the feasibility of maintaining N. affinis on a small scale for a long period using cheaply available culture vessels. Within six weeks (42 days) a minimum harvest of 43.6 x 103 copepod.L-1 and maximum of 44.5 x 103 copepod.L-1 were obtained. Using several numbers of vessels (2L-capacity) for mass production, it was feasible to harvest 15.0 x 103 copepod.L-1 daily after two weeks of inoculation. Nitocra affinis has a great potential as live food because it contained high protein (39 to 52%), lipid (13 to 23%) and carbohydrates (8 to 11%). It also contained high level of n-3 HUFA (up to 44%) and n-6 HUFA (up to 14%). In addition it contained high amount of DHA (up to 19%) and EPA (up to 25%). Moreover, levels and ratios of fatty acids closely matched both the requirements of marine finfish and shrimp larvae.